The development of student worksheets using ethnomatematics based prediction, observation, and explanation learning models to improve student's critical thinking ability - Mania, Sitti; Jamaluddin, Nazurah; Kusumayanti, Andi; Nur, Fitriani (Desimal: Jurnal Matematika, 2021)
This research is a research and development that aims to develop and assess the quality of student worksheets (LKPD) using ethnomathematics-based prediction, observation, and explanation (POE) learning models to improve students' mathematical critical thinking abilities that are valid, practical, and effective. This research is a development research that refers to the ADDIE development model, namely, analysis, design, development, implementation, and evaluation. In this research, the test subjects were students of class VIII G MTs Al-Urwatul Wutsqaa Sidrap Regency with 26 students. Based on the results of the trials that have been carried out, it is found that (a) The validation of LKPD and other instruments are 3.78 in the "very valid" category, (b) Practical based on the average percentage for the implementation of LKPD has 1.93 of average with the implemented category. Overall, the percentage of the average student response is 93.75% with a very positive category, and the average teacher response is 100% with a very positive category. Thus, the developed LKPD meets practical criteria. (c) Effective because the average percentage of students’ activity is 84.13% with the very good category, the average ability to manage learning is 4.1 in the good category. The average percentage of student learning outcomes tests on critical thinking abilities is 78.6.  Therefore, it could be said that students' critical thinking abilities used LKPD is good. It can be concluded that the trial phase which was carried out using the ethnomathematics-based student worksheet of POE learning models to improve students' critical mathematical abilities had met the criteria of validity, practicality and effectiveness.